Control and remote monitoring of the vertical machining center by using the OPC UA protocol. Issue 3 (September 2020) - Martinov, G M; Nikishechkin, P A; Khoury, A Al; Issa, A
Abstract: The article discusses the possibilities of using the OPC UA protocol to collect information from CNC machines and graphically represent data about the technological process, according to Industry 4.0 concept. A generalized organization structure of NC kernel with an embedded SoftPLC module, OPC UA server and various types of OPC UA clients has been developed. The mechanism of interaction between the NC kernel and the standalone OPC UA server is proposed. The possibility of developing a remote OPC UA web client based on the Node-red programming tool has been investigated.